Des enseignants qui res(is)tent : dynamiques identitaires et investissement du champ de l’enseignement professionnel au Québec - Sophie Grossmann (Recherches en Éducation)
Teacher attrition has been the focus of much research and policies in the last decades. Echoing the issue of students leaving school prematurely, that of teachers leaving the profession during their first years of practice has mobilized a number of stakeholders and academics in charge of teacher education and induction. Though teachers at large face similar difficulties when their enter the profession (initial work complexity and workload, precarious status...), Quebec’s high school vocational teachers’ entry into the teaching profession brings about its own lot of difficulties, among which a rapid transition from a trade they practised to teaching that may be experienced as a painful break from their original occupational field. In this article, a shift in perspective leads us to interrogate those teachers who, against significant odds, persist beyond the critical first five years of vocational teaching practice. How does their transition deploy between a before as a professional in their trade and an after as a teacher? Based on in-depth interviews collected among eighteen vocational teachers, the analysis focuses on identity and professional transition processes with regards to teachers’ socioprofessional itineraries.